When Does Sharing Stigmatize? Saving Money (vs. Seeking Variety) Through Access-Based Consumption - Guo, Yang Jenny; Lamberton, Cait (Frontiers in Psychology, 2021)
Access-based services allow financially-constrained individuals to consume a variety of goods and services without the cost of sole ownership. But might there be dangers in communicating about access-based consumption in terms of its affordability, particularly among this segment of consumers? To answer this question, we investigate the effects of framing access-based consumption in terms of two primary benefits: affordability and variety. Results from four studies suggest that although affordability might rationally be of most interest to financially-constrained individuals, framing access-based consumption’s benefits in terms of affordability undermines the happiness they may extract from their consumption relative to framing in terms of variety. This difference emerges because communications focused on affordability re-affirm the negative self-identity financially-constrained individuals perceive as a result of their financial situation. Given these findings, we make clear recommendations for communications related to the access-based economy and this vulnerable set of people.